(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Some struggle with choosing their path. They will find work or go to college. Others go to college either by choice or by force, and some would rather begin their careers as employees or business owners. However, there is a third option, where one can do both: become a working student, when hard work must be present to get the desired diploma and to pursue their life dreams. Previous studies do not explain or describe how coping mechanisms assist working college students in performing well academically. As a result, the purpose of this study was to address a research gap by obtaining additional information about how college- working students, specifically engineering-working students, manage stress and what their coping techniques are. The results obtained from the data gathering were done through a series of interview sessions with 4th-year college engineering working students, who were the chosen respondents of the study. The study found that students use extracurricular activities as a stress-relieving strategy. This research also concludes that the stressors that students experience have a huge impact on their academics. However, by using time management methods, students are able to balance their academic and work duties. The majority of study participants provided insight into the complex and varied ways individuals deal with difficult circumstances. Different coping mechanisms were used by the study’s participants. The data gathered in this study highlights numerous important stresses that have an effect on individuals across a range of circumstances. One of the issues that came up most frequently was time management.